Effect of sialylation on EGFR phosphorylation and resistance to tyrosine kinase inhibition - Yen, Hsin-Yung; Liu, Ying-Chih; Chen, Nai-Yu; Tsai, Chia-Feng; Wang, Yi-Ting; Chen, Yu-Ju; Hsu, Tsui-Ling; Yang, Pan-Chyr; Wong, Chi-Huey (Proceedings of the National Academy of Sciences - PNAS, 2015)
Epidermal growth factor receptor (EGFR) is a heavily glycosylated transmembrane receptor tyrosine kinase. Upon EGF-binding, EGFR undergoes conformational changes to dimerize, resulting in kinase activation and autophosphorylation and downstream signaling. Tyrosine kinase inhibitors (TKIs) have been used to treat lung cancer by inhibiting EGFR phosphorylation. Previously, we demonstrated that EGFR sialylation suppresses its dimerization and phosphorylation. In this report, we further investigated the effect of sialylation on the phosphorylation profile of EGFR in TKI-sensitive and TKI-resistant cells. Sialylation was induced in cancer progression to inhibit the association of EGFR with EGF and the subsequent autophosphorylation. In the absence of EGF the TKI-resistant EGFR mutant (L858R/T790M) had a higher degree of sialylation and phosphorylation at Y1068, Y1086, and Y1173 than the TKI-sensitive EGFR. In addition, although sialylation in the TKI-resistant mutants suppresses EGFR tyrosine phosphorylation, with the most significant effect on the Y1173 site, the sialylation effect is not strong enough to stop cancer progression by inhibiting the phosphorylation of these three sites. These findings were supported further by the observation that the L858R/T790M EGFR mutant, when treated with sialidase or sialyltransferase inhibitor, showed an increase in tyrosine phosphorylation, and the sensitivity of the corresponding resistant lung cancer cells to gefitinib was reduced by desialylation and was enhanced by sialylation. Significance This report reveals the influence of sialylation on the activation of epidermal growth factor receptor (EGFR) and sensitivity to tyrosine kinase inhibitors (TKIs) against EGFR phosphorylation. By utilizing biochemical approaches, we demonstrated that EGFR sialylation suppresses EGFR phosphorylation by inhibiting EGF binding and EGFR dimerization. In the TKI-resistant lung cancer cell line with L858R/T790M mutations on EGFR, the levels of phosphorylation at Y1068, Y1086, and Y1173 are upregulated, and sialylation can partially suppress the phosphorylation of EGFR at these sites and enhance EGFR sensitivity to TKI. These findings suggest that sialylation has an important role in tumorigenesis and sensitivity to TKIs by modulating EGFR phosphorylation and the associated signaling network and provide insights for therapeutic intervention.